Kedudukan Ilmu Ekonomi Islam di antara Ilmu Ekonomi dan Fikih Muamalah: Analisis Problematika Epistemologis - Azwar Iskandar; Khaerul Aqbar (Pusat Penelitian dan Pengabdian Masyarakat (P3M) Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2019)
The objectives of this research are to examine the economics and fikih muamalah based on epistemology paradigm, analyze the epistemological problems that appear from the existance of Islamic economics between the effect of the economics and fikih muamalah, and give solutions of its epistemological problems especially in higher education institution environment. This research use descriptive-qualitative approach method with content analysis dan library research technique. The results show that : (1) the Islamic economics is not just a system or norm but also it is a knowledge that founded by scientific methodology; (2) the existance of Islamic economics between the effect of the economics and fikih muamalah cause the epistemological problems i.e. how to mix between the economics sourced from human thoughts and the fikih muamalah sourced from the God values; (3) the fundamental difference between economics and fikih muamalah especially in epistemological terms require the thought to make a synergy in Islamic economics with re-definition toward both of them.